Evaluation of fecal calprotectin as a marker of gastrointestinal inflammation in rosacea: A case-control study - (:unkn) unknown (WILEY, 2021)
A higher incidence of gastrointestinal diseases has been well established in patients with rosacea. However, no screening tool has been introduced for gastrointestinal disease development in rosacea. Fecal calprotectin (FC) is a calcium-binding protein, mainly derived from polymorpho-nuclear cells, such as neutrophils. It has been established as a marker of gastrointestinal inflammation. The aim of the present study was to evaluate FC levels in patients with rosacea without any gastrointestinal diseases. A prospective, case-control study was planned to investigate the relationship between rosacea and gastrointestinal involvement by evaluating FC levels and the Gastrointestinal Symptom Rating Scale (GSRS). A total of 47 patients with rosacea and 39 healthy control subjects were included in the study. The FC levels were statistically significantly higher in rosacea group than in the control group (65.96 +/- 58.86 ng/mL vs 31.99 +/- 20.12 ng/mL, P = .026, respectively). A statistically significant difference was also observed in GSRS values between the patient and the control groups (30.26 +/- 12.48 vs 22.62 +/- 7.64, P = .001, respectively). A positive correlation was noted between FC levels and the values of GSRS in the study group (r: 0.354; P = .001) and in the rosacea group (r = 0.392, P = .006). The measurement of FC may be useful in the early detection of gastrointestinal system diseases that may accompany rosacea and may provide a pathway to develop treatment strategies targeting both skin and intestinal mucosa.
Keywords: fecal calprotectin; gastrointestinal disease; inflammation; rosacea; the gastrointestinal symptom rating scale